EVALUASI PELAKSANAAN KEBIJAKAN PEMBAYARAN NON TUNAI PADA BUS TRANS METRO PEKANBARU TAHUN 2023 - Nst, Amesza Ghadijah; Yusri, Ali (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study is based on Pekanbaru Mayor Regulation Number 26 of 2019 concerning Guidelines for the Implementation of Electronic Ticketing on the Trans Metro Pekanbaru Mass Transportation System. The implementation of the cashless payment policy on Trans Metro Pekanbaru has led to a decline in the number of bus passengers, which in turn has contributed to a decrease in Regional Original Revenue. Although the policy aims to improve service efficiency and modernization, its implementation in the field has generated several issues, including limited infrastructure, low digital literacy among the public, and uneven access to digital services. This research employs a qualitative approach with a descriptive method, using data collected through interviews, observations, and documentation. The study was conducted in Pekanbaru City, specifically at the UPT TMP of the Pekanbaru City Transportation Agency. The evaluation of the policy's success is based on William N. Dunn’s policy evaluation theory. The findings of this study indicate that the cashless payment policy on Trans Metro Pekanbaru is a government initiative to adapt to digital-era developments. However, its implementation has not been fully optimal. In terms of effectiveness and efficiency, the policy continues to face technical obstacles and has not significantly increased the number of users. The aspects of adequacy and equity have also not been fulfilled, as facilities and policy outreach have not reached all segments of society. From the perspective of responsiveness, the government has not fully addressed users’ more urgent needs, such as bus punctuality and the comfort of bus stops. Meanwhile, regarding policy accuracy, the initiative is relevant to digitalization trends but has yet to align fully with the social conditions of Pekanbaru’s population. Keywords: Evaluation, Policy, Cashless Payment